Geometries of Nation-Building: Triangulating Female Homosociality in Richardson’s Wacousta - Fox, L. Chris (Studies in Canadian Literature, 2002)
Female homosociality is critical to the theme of nation-building in Wacousta but, unlike male homosociality, has been almost entirely overlooked in critical treatments of the novel. The novel’s ending, for instance, suggests that only the white characters who have indigenized through the agency of cross-cultural female homosociality survive to produce a "Canadian" generation. The challenge of such female-dominated homosocial triangles (for example, Oucanasta-Frederick-Madeline) to male-dominated homosocial triangles (Charles-Everard-Clara) is significant in that it deviates from European literary patterns, replacing the patriarchal structure of old-world society with a community that instead emphasizes strong female and native influences.